Predictors for abundance of host flea and floor flea in households of villages with endemic commensal rodent plague, Yunnan Province, China. - Jia-Xiang Yin; Alan Geater; Virasakdi Chongsuvivatwong; Xing-Qi Dong; Chun-Hong Du; You-Hong Zhong (Public Library of Science (PLoS), 2011)
BACKGROUND: From 1990 to 2006, fifty-five natural villages experienced at least one plague epidemic in Lianghe County, Yunnan Province, China. This study is aimed to document flea abundance and identify predictors in households of villages with endemic commensal rodent plague in Lianghe County. METHODS: Trappings were used to collect fleas and interviews were conducted to gather demography, environmental factors, and other relevant information. Multivariate hurdle negative binomial model was applied to identify predictors for flea abundance. RESULTS: A total of 344 fleas were collected on 101 small mammals (94 Rattus flavipectus and 7 Suncus murinus). R. flavipectus had higher flea prevalence and abundance than S. murinus, but the flea intensities did not differ significantly. A total of 315 floor fleas were captured in 104 households. Xenopsylla cheopis and Ctenocephalides felis felis were the predominant flea species on the host and the floor flea, respectively. The presence of small mammal faeces and R. flavipectus increased host flea prevalence odds 2.9- and 10-fold, respectively. Keeping a dog in the house increased floor flea prevalence odds 2-fold. Keeping cattle increased floor flea intensity by 153%. Villages with over 80% of houses raising chickens had increased prevalence odds and intensity of floor flea about 2.9- and 11.6-fold, respectively. The prevalence and intensity of floor flea in brick and wood houses were decreased by 60% and 90%, respectively. Flea prevalences of host and floor flea in the households that were adjacent to other houses were increased 7.4- and 2.2-fold, respectively. Houses with a paddy nearby decreased host flea intensity by 53%, while houses with an outside toilet increased host flea intensity by 125%. CONCLUSION: Rodent control alone may not be sufficient to control plague risk in these areas. In order to have successful results, plague control programs should pay attention to ecological and hygiene factors that influence flea populations.